GPCRs in Autocrine and Paracrine Regulations - Tse, Lap Hang; Wong, Yung Hou (Frontiers in Endocrinology, 2019)
G protein-coupled receptors (GPCRs) constitute the largest superfamily of integral membrane protein receptors. As signal detectors, the several hundred known GPCRs are responsible for sensing the plethora of endogenous ligands that are critical for the functioning of our endocrine system. Although GPCRs are typically considered as detectors for first messengers in classical signal transduction pathways, they seldom operate in isolation in complex biological systems. Intercellular communication between identical or different cell types is often mediated by autocrine or paracrine signals that are generated upon activation of specific GPCRs. In the context of energy homeostasis, the distinct complement of GPCRs in each cell type bridges the autocrine and paracrine communication within an organ, and the various downstream signaling mechanisms regulated by GPCRs can be integrated in a cell to produce an ultimate output. GPCRs thus act as gatekeepers that coordinate and fine-tune a response. By examining the role of GPCRs in activating and receiving autocrine and paracrine signals, one may have a better understanding of endocrine diseases that are associated with GPCR mutations, thereby providing new insights for treatment regimes.